When Women Disrupt Prayer? Rethinking a Controversial Hadith through Al-Adlabi’s Matan Criticism - Wathani, Muhammad Fadhil; Ahmad Musyafiq; Nikmah Rochmawati; Mahadi Rahman; Zufriyatun (JOURNAL OF QUR'AN AND HADITH STUDIES, 2025)
The hadith that mentions women, donkeys, and dogs can cancel prayers when passing in front of people who pray has caused controversy, mainly because it is considered to contain gender bias. This study aims to examine the validity of the matan hadith through the approach of matan criticism according to al-Adlabi in Manhaj Naqd al-Matn 'Inda 'Ulamā' al-Ḥadīth al-Nabawī. The method employed is a literature study that involves tracing the hadith in al-Kutub al-Tis'ah and analyzing it based on four criteria: conformity with the Qur'an, sahih hadith, the Prophet's sirah, rationality, and historical context, as well as editorial feasibility. The results of the analysis show that, although the sanad of the hadith is considered authentic, it contains problems: it is not in line with the Qur'an, it contradicts Aisha's history and the Prophet's practice, and it juxtaposes women with animals in the context of worship. This study emphasizes the importance of critically analyzing the hadith so that our understanding of it remains in harmony with the values of justice, common sense, and humanity in Islam.